The Legend of Rothschild as the “Napoleon of Finance” in Dostoevsky’s Novel The Idiot - Nikolai N. Podosokorsky (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article analyzes the Rothschild theme in the novel The Idiot, a motif strictly connected with the myth of Napoleon, in which Dostoevsky was keenly interested during all his artistic life. Both Napoleon’s and Rothschild’s features pertain to Napoleonic heroes such as Ganya Ivolgin and Ippolit Terentev. Moreover, in the novel, the historical and cultural fusion of Napoleon and Rothschild becomes more complex because of the references to different representatives of the Rothschild dynasty and to different Napoleons – Napoleon I and Napoleon III, governor of France at that time. Dostoevsky was critic both to Bonaparte and Rothschild, as in their views he detected a fundamental deviation from the core of Christianism. Dostoevsky considered the motif of the power of money and Mammon’s greatness as one of the severest problems of the 19th century, “a cruel time, a time of business and money, a calculating time, full of tables, numbers, and zeros of all kinds and types”. Since his first works, Dostoevsky relates the Napoleonic idea with the idea of enrichment (“Mr. Prokharchin”, “Uncle’s dream”, Crime and Punishment, and others). However, in Dostoevsky’s early works the names of Napoleon and Rothschild developed rather parallel to each other and fused together later in the novels The Idiot and The Adolescent.